Highlighting Global Peace and Harmony in Muslim Scholars’ Religious Discourse: A Positive Discourse Analysis - Younas, Muhammad; Maqbool, Saira (Pakistan Languages and Humanities Review, 2025)
This paper aims at highlighting the moderate ideologies in Muslim Scholars’ religious discourse. The background of the study is religion as an important social institution that not only produces and controls religious discourse but also form opinion of its audience. Furthermore, religion motivates its audience for desired actions. That’s why it becomes significant to analyze religious discourse. In this study, qualitative methods have been used to analyze the speeches of the Muslim Scholars from the lens of positive discourse analysis known as PDA. PDA is a sub-discipline of critical discourse analysis known as CDA. The data of this study was the speeches of Muslim scholars that was collected through purposive sampling. The speeches were directly addressed in English. The Data was secondary in nature since it was downloaded from YouTube. Key findings of this research are very profound. The dominant themes that emerged from the speeches of Muslim scholars were peace and harmony both at local and global levels. Finally on the basis of results, certain recommendations are made in relation to religious discourse of Muslim Scholars. These recommendations may be valuable for the peace-building through interfaith harmony and interfaith dialogue. The study recommends that these moderate discourses can be used by peace organizations that working for interfaith harmony and peace-building. It is also recommended that such moderate discourses should be encouraged and promoted by the governments. These moderate discourses should also be highlighted by media houses so that religious extremism and radicalization may be dissuaded.